STRATEGI MANAJEMEN KESISWAAN DALAM MENGATASI KRISIS DISIPLIN DAN KECANDUAN MEDIA SOSIAL PADA PESERTA DIDIK - Dwi Putri Achliyanda; Apta Fathul Aini Prasya; Desiawan Budi Eko Sanjaya; Yudi Ismanto (STKIP Pesisir Selatan, 2026)
The development of digital technology and the increasingly intensive use of social media have influenced student behavior, particularly in aspects of discipline and self-control. Excessive use of social media has the potential to reduce learning concentration, compliance with school regulations, and increase addictive behavior. This study aims to analyze student management strategies in addressing the discipline crisis and social media addiction among students in the digital era. The study used a qualitative approach with the Library Research method (literature study). Data sources were obtained from accredited national journals, reputable international journals, and relevant books for the period 2021–2026. Data were analyzed using thematic analysis techniques through the stages of data collection, selection, reduction, categorization, interpretation, and synthesis. The results show that effective student management strategies include strengthening character-based discipline, developing digital literacy, optimizing guidance and counseling services, strengthening extracurricular activities, and collaboration between schools and parents. These strategies can support the formation of disciplined behavior and healthier use of social media. The novelty of this research lies in the development of a Digital Character-Based Integrative Student Management Model that integrates preventive, curative, and digital character development.